2013
DOI: 10.1117/1.jbo.18.8.087001
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy, a potential tool in diagnosis and prognosis of castration-resistant prostate cancer

Abstract: Abstract. Purpose: We evaluated the feasibility of Raman spectroscopy (RS) in diagnosis and prognosis of castration-resistant prostate cancer (CRPC) in patients with prostate cancer (PC). Materials and methods: Raman spectra are detected from PC cell lines (LNCaP and C4-2) and tissues using a Labram HR 800 RS. Then, principal component analysis (PCA) and support vector machine (SVM) are applied for prediction. A leave-one-out cross-validation is used to train and test the SVM. Results: There are 50 qualified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 34 publications
(40 reference statements)
0
33
0
Order By: Relevance
“…The complete Raman frequency assignment of spectra recorded is presented in Table 1. [29][30][31][32][33][34][35][36] As a consequence of the induction of oxidative DNA fragmentation, shown in Fig. 2(B), we found major differences in the corresponding Raman spectral profiles, specifically, alterations within the 600-1700 cm À1 spectral range, which includes that band associated with the DNA phosphate backbone.…”
Section: Resultsmentioning
confidence: 89%
“…The complete Raman frequency assignment of spectra recorded is presented in Table 1. [29][30][31][32][33][34][35][36] As a consequence of the induction of oxidative DNA fragmentation, shown in Fig. 2(B), we found major differences in the corresponding Raman spectral profiles, specifically, alterations within the 600-1700 cm À1 spectral range, which includes that band associated with the DNA phosphate backbone.…”
Section: Resultsmentioning
confidence: 89%
“…Peaks at 685, 730, 790, 1252, 1305, 1337, 1376, 1421, 1486 and 1662 cm -1 belonged to the characteristic Raman spectra of bases. And peaks at 950, 993 and 1445 cm -1 contributed to the desoxyribose and phosphodiester groups, together with the stretching vibration banding at 1052 and 1612 cm -1 [35][36][37][38][39][40][41][42] . …”
Section: Resultsmentioning
confidence: 99%
“…There are many studies that have shown that PCA and Raman spectroscopy are a powerful technique in several diseases as a diagnostic tool . PCA was used to find the main principal components that maximize the variance of the most important features of Raman spectra of diabetics and healthy patients.…”
Section: Resultsmentioning
confidence: 99%